Intracellular S100A9 Promotes Myeloid-Derived Suppressor Cells during Late Sepsis - Dai, Jun; Kumbhare, Ajinkya; Youssef, Dima; McCall, Charles E.; Gazzar, Mohamed El (Frontiers in Immunology, 2017)
Myeloid precursor cell reprogramming into a myeloid-derived suppressor cell (MDSC) contributes to high mortality rates in mouse and human sepsis. S100A9 mRNA and intracellular protein levels increase during early sepsis and remain elevated in Gr1+CD11b+ MDSCs after pro-inflammatory sepsis transitions to the later chronic anti-inflammatory and immunosuppressive phenotype. The purpose of this study was to determine whether intracellular S100A9 protein might sustain Gr1+CD11b+ MDSC repressor cell reprogramming during sepsis. We used a chronic model of sepsis in mice to show that S100A9 release from MDSCs and circulating phagocytes decreases after early sepsis, and that targeting the S100a9 gene improves survival. Surprisingly, we find that intracellular S100A9 protein translocates from the cytosol to nucleus in Gr1+CD11b+ MDSCs during late sepsis and promotes expression of miR-21 and miR-181b immune repressor mediators. We further provide support of this immunosuppression pathway in human sepsis. This study may inform a new therapeutic target for improving sepsis outcome.